The Effectiveness of the Use of Drugs from the Nitrofuran Group in the Treatment of Acute Pyelonephritis in Children - R. M., Nuraliyeva; Z., Mirzaqulov; Bobur, To’layev; Bobur, To’layev (American Journal of Biomedicine and Pharmacy, 2025)
Acute pyelonephritis remains one of the most frequent infectious inflammatory diseases of the urinary system in children, leading to high morbidity and potential long-term renal complications. The purpose of this study was to evaluate the clinical efficacy and safety of nitrofuran-class agents, primarily nitrofurantoin, in pediatric acute pyelonephritis. A clinical observational analysis was performed on 118 hospitalized pediatric patients aged 2–14 years. All patients received nitrofurantoin as part of combination antibacterial therapy. Clinical, laboratory, and instrumental parameters were monitored. The results demonstrated a significant decrease in inflammatory markers, rapid regression of clinical symptoms, and low recurrence rate during follow-up. Nitrofurantoin showed high efficacy in eliminating urinary pathogens, predominantly Escherichia coli strains, with minimal adverse reactions. These findings confirm the importance of nitrofuran derivatives in pediatric nephrology practice, particularly for treating lower and upper urinary infections and preventing progression to chronic renal pathology. Acute pyelonephritis in the pediatric population represents a challenging clinical condition requiring rapid and targeted antimicrobial intervention to prevent renal damage and reduce recurrence. This research focused on the therapeutic relevance of nitrofuran derivatives, with emphasis on nitrofurantoin, in children diagnosed with acute pyelonephritis. Monitoring of clinical indicators, laboratory biomarkers, and microbiological clearance demonstrated substantial improvement throughout therapy. Notably, nitrofuran treatment led to decreased inflammatory responses, stabilization of renal function parameters, and sustained pathogen eradication. Its favorable tolerability profile and reduced antimicrobial resistance potential highlight its justification as a primary pharmacologic decision in pediatric urinary infections.